Gender, Sexuality, and Risk in the Practice of Affective Labour for Young Women in Bar Work. (December 2018) - Coffey, Julia; Farrugia, David; Adkins, Lisa; Threadgold, Steven
This article explores the ways that gender, sexuality, pleasure, and risk are entangled in affective labour and the production of value in 'front of house' bar work. Through their work as bar staff at 'hip' inner-city Melbourne venues, the young women we discuss produce affects in the form of a 'vibe' of relaxation, fun, pleasure, and release. We address McRobbie's call for the 'actual working practices' which comprise affective labour to be explored and highlight the ways gender relations including the heterosexual matrix of desire are mobilised in the production of value in young women's bar work. We discuss the tensions at play in this context where women are required to generate both a positive and a pleasurable feeling in their interactions with others while negotiating the complex politics of heterosexual desire while at work, including managing and negotiating harassment from male customers. This management requires complex sensate and embodied practices that are both conscious and unconscious (described, for example, as an 'instinct'), involving constantly 'scanning' and 'reading the crowd' and monitoring their own embodied and affective responses to particular men while they carry on other conversations or pour drinks. We argue it is critical to study the 'actual working practices' which comprise affective labour in order to expose the ways relations of inequality can be mobilised in the production of value in this context.